METABOLIC MEDICATIONS FOR THE REHABILITATION OF CHILDREN BORN TO DRUG ADDICTED WOMEN - A.A. Dzhumagaziev; N.V. Sibiryakova; E.I. Kazimirova (Union of pediatricians of Russia, 2007)
The authors presented the study results of the physical and neuro psychic growth of children, who were born to drug addicted women. they studied the active state of the dehydrogenase peripheral blood lymphocytes, reflecting the metabolic disorder at the tissue level and body level in general, as well as the ways to correct them with metabolic therapy assisted by glycine and biotredin. They also analyzed the results of the complex therapy and rehabilitation of the children, who were born to drug addicted women.Key words: drug embryopathy, metabolic therapy, children, rehabilitation.